posted by Allyson on .
So I have to solve this problem
And then I wrote down:
but I don't know what to do from there, can someone explain to me please?
The next step is to combine like terms and get the knowns on one side and the unknowns on the other.
Subtract 6a from both sides of the equation.
9a - 6a = 6a - 6a + 24
3a = 24
Divide both sides by 3 to find the value of a.
3a/3 = 24/3
a = 8
Okay, when I checked my answer, how come I got 72? when I put 8 As A into the equation.
That's what the original problem states: 72 = 72
9(8) = 6(8 + 4)
72 = 72
So I could have two answers... ? 8 and 72?
You only need to find what a represents. As we found, in this problem a = 8.
You proved it by substituting 8 for a in the original problem.